Maternal Fatty Acids and Their Association with Birth Outcome: A Prospective Study - Meher, Akshaya (PLoS One, 2016)
Maternal nutrition, especially LCPUFA, is an important factor in determining fetal growth and development. Our earlier cross sectional study reports lower docosahexanoic acid (DHA) levels at the time of delivery in mothers delivering low birth weight (LBW) babies. This study was undertaken to examine the role of the maternal omega-3 and omega-6 fatty acid profile across the gestation in fetal growth. This is a hospital based study where women were recruited in early gestation. Maternal blood was collected at 3 time points, i.e., T1 = 16(th)–20(th) week, T2 = 26(th)–30(th) week and T3 = at delivery. Cord blood was collected at delivery. At delivery, these women were divided into 2 groups: those delivering at term a baby weighing >2.5kg [Normal birth weight (NBW) group] and those delivering at term a baby weighing <2.5kg [LBW group]. The study reports data on 111 women recruited at T1, out of which 60 women delivered an NBW baby at term and 51 women delivered an LBW baby at term. Fatty acids were analysed using gas chromatography. At T1 of gestation, maternal erythrocyte DHA levels were positively (p<0.05) associated with baby weight. Maternal plasma and erythrocyte arachidonic acid and total erythrocyte omega-6 fatty acid levels at T2 were higher (p<0.05 for both) in the LBW group. Total erythrocyte omega-3 fatty acid levels were lower (p<0.05) while total erythrocyte omega-6 fatty acid levels were higher (p<0.05) in the LBW group at delivery. Our data demonstrates the possible role of LCPUFA in the etiology of LBW babies right from early pregnancy.